The Impact of Technology Orientation on The Performance of Administrative staff of NCD (the National Center for Distinguished)In SYRIA - Gadeer, Basem; Daghman, Loubna (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aims to measure the degree to which the National Center for distinguished market-oriented by measuring the degree of orientation technology at the administrative level to serve the students and staff working in it needs (customers). And to discover the impact of technology on the performance orientation center representative management effectiveness, and If this effect is different depending on the demographics of the members of the sample, The researchers developed a tool with reference to the literature and research articles related to the topic of research to measure the variables mentioned using a component of the 25-item questionnaire form. Results show that There was a relationship between technology orientation in the NCD and the effective management practices. And it was clear that demographic factors affect the administrative cadre in the NCD on the level of technology oriented administrative staff and on the degree of the impact of this trend on effective management practices. تأثير التوجّه بالتكنولوجيا على أداء الكادر الإداري للمركز الوطني للمتميزين في سورية هدفت الدراسة إلى قياس درجة توجّه المركز الوطني للمتمّيزين بالسوق لخدمة احتياجات الطلاب والكوادر العاملة فيه (العملاء)، وذلك من خلال قياس درجة توجّهه بالتكنولوجيا كمؤشر جزئي من التوجه بالسوق وذلك في المستوى الإداري. وإلى دراسة تأثير التوجّه بالتكنولوجيا على أداء المركز ممثلاً بأداء الكادر الإداريّ، واختلاف هذا التأثير باختلاف العوامل الديموغرافية لأفراد العينة،وتمّ تطوير أداة الدراسة بالرجوع إلى الأدبيات والمقالات البحثية المرتبطة بموضوع البحث لقياس المتغيرات المذكورة باستخدام استمّارة استبيان مكون من 25 بنداً.وقد تبين وجود علاقة بين التوجّه بالتكنولوجيا في NCD وبين أداء الكادر الإداريّ. وتؤثر العوامل الديموغرافية للكادر الإداري في NCD على مستوى توجّهه بالتكنولوجيا وعلى درجة تأثير هذا التوجّه على أداء الكادر المذكور.